Cross-disciplinary model for yacht interior design: Integration of traditional visualisation and virtual reality technology - Matiyko, N.; Matiyko, O.; Koval, S.; Danylchenko, N. (Art and Design, 2025)
The aim was to investigate a cross-disciplinary model of yacht interior design in the context of the methodological integration of traditional visualisation methods and virtual and augmented reality tools. The study employed an interdisciplinary approach, systems analysis, and comparative methods, which allowed for structuring the integration of traditional visualisation and virtual reality tools, as well as identifying key interrelations between them. The study proved that the integration of traditional visualisation methods with virtual and augmented reality technologies significantly increases the efficiency of the yacht interior design process, improves the accuracy of modelling, and contributes to a better perception of the final result. It was noted that the role of traditional tools is not diminishing, but, on the contrary, is gaining new opportunities when used in conjunction with the latest arsenal of design tools. In addition, it was found that the use of a cross-disciplinary model contributes to a deeper understanding of design solutions, accelerates the processes of coordination and implementation, and expands the possibilities for optimising the functional and aesthetic characteristics of the interior. New approaches to the integration of visual aspects of design have been identified, revealing the potential of using a cross-disciplinary model for a deeper understanding and evaluation of interior design solutions. The prospect of effectively combining various visualisation tools has been outlined, which allows for improving the process of interaction between designers, engineers and customers. The current study has proposed a theoretical basis for further development and implementation of a modern approach to design that takes into account both traditional and innovative means of presenting visual information. The practical significance of the results lies in their application to yacht interior design, educational programs for specialists in marine design, architecture, and visual arts, as well as in the development of innovative approaches to the visualisation of design solutions